Factors associated with benign multiple sclerosis in the New York State MS Consortium (NYSMSC). Issue 1 (December 2016) - Zivadinov, Robert; Cookfair, Diane; Krupp, Lauren; Miller, Aaron; Lava, Neil; Coyle, Patricia; Goodman, Andrew; Jubelt, Burk; Lenihan, Michael; Herbert, Joseph; Gottesman, Malcolm; Snyder, David; et al.
Abstract Background This retrospective analysis explored prognostic factors associated with a benign multiple sclerosis (BMS) disease course at baseline and over the 4-year follow-up. Methods Patients from the centralized New York State Multiple Sclerosis Consortium registry were classified as having BMS according to 3 different criteria centered on disease duration and disability. Additional analyses explored prognostic factors associated with BMS using the most conservative disability criteria (Expanded Disability Status Scale ≤2 and disease duration ≥10 years). Results Among 6258 patients who fulfilled eligibility criteria, 19.8 % to 33.3 % were characterized as having BMS, at baseline depending on classification criteria used. Positive prognostic factors for BMS at baseline included female sex (p <  0.0001) and younger age at onset (p <  0.0001); negative prognostic factors included progressive-onset type of MS and African-American race. Of the 1237 BMS patients (per most conservative criteria), 742 were followed for a median of 4 years to explore effect of disease-modifying treatment (DMT) on benign status. DMT (p =  0.009) and longer disease duration (p =  0.007) were the only significant positive predictors of maintaining BMS at follow-up. The protective effect was stronger for patients taking DMT at both enrollment and follow-up (OR = 0.71;p  = 0.006). Conclusions There is a need for development of more reliable prognostic indicators of BMS. Use of DMT was significantly associated with maintaining a benign disease state.